PERILAKU MINUM JAMU PADA IBU NIFAS BERDASARKAN TEORI “SUNRISE MODEL― - Maulida Puteri Kusumadewi; Esti Yunitasari; Ni Ketut Alit (Pediomaternal Nursing Journal, 2014)
Postpartum is a recovery period of returning maternal reproductive organs to the normal form around 6 weeks or 42 days.In Ponkesdes Pademawu Barat Kabupaten Pamekasan, the mothers often use Madurese traditional herbal drinks in thepostpartum period. The purpose of this study was to analyze the correlation between herbal drinking behavior topostpartum mothers with transcultural nursing theory. The study design used was descriptive analytic design withpurposive sampling technique. Respondents of this study consisted of 18 respondents. The independent variables in thisstudy were the education background and cultural values, while the dependent variable were knowledge, attitudes, andactions of herbal drinking. The research was conducted from 23 to 27 May 2014 at Ponkesdes Pademawu BaratPamekasan. The statistical test used were Chi square and Spearman's Rho correlation test. The result showed that therewas a correlation between educational background with knowledge of herbal drinking to postpartum mother (p = 0.020),attitude (p = 0.014), and actions (p = 0.014). There is a correlation between cultural values with knowledge of herbaldrinking to postpartum mother (p = 0.018), attitudes (p = 0.007), and actions (p = 0.004). It can be concluded that thebehavior of herbal drinking to postpartum mother correlated with trancultural nursing theory that educational backgroundand cultural value. For further research, can be researched correlation of economic factors, social, political and law,religion and philosophy, technology with postnatal behavior in the other areas